Occipital nerve block for the short-term preventive treatment of migraine: A randomized, double-blinded, placebo-controlled study. (October 2015) - Dilli, Esma; Halker, Rashmi; Vargas, Bert; Hentz, Joseph; Radam, Teresa; Rogers, Robert; Dodick, David
Background: Occipital nerve (ON) injections with corticosteroids and/or local anesthetics have been employed for the acute and preventive treatment of migraine for decades. However, to date there is no randomized, placebo-controlled evidence to support the use of occipital nerve block (ONB) for the prevention of migraine. Objective: The objective of this article is to determine the efficacy of ONB with local anesthetic and corticosteroid for the preventive treatment of migraine. Participants and methods: Patients between 18 and 75 years old with ICHD-II-defined episodic (> 1 attack per week) or chronic migraine (modified ICHD-II as patients with > 10 days with consumption of acute medications were permitted into the study) were randomized to receive either 2.5 ml 0.5% bupivacaine plus 0.5 ml (20 mg) methylprednisolone over the ipsilateral (unilateral headache) or bilateral (bilateral headache) ON or 2.75 ml normal saline plus 0.25 ml 1% lidocaine without epinephrine (placebo). Patients completed a one-month headache diary prior to and after the double-blind injection. The primary outcome measure was defined as a 50% or greater reduction in the frequency of days with moderate or severe migraine headache in the four-week post-injection compared to the four-week pre-injection baseline period. Results: Thirty-four patients received active and 35 patients received placebo treatment. Because of missing data, the full analysis of 33 patients in the active and 30 patients in the placebo group was analyzed for efficacy. In the active and placebo groups respectively, the mean frequency of at least moderate (mean 9.8 versus 9.5) and severe (3.6 versus 4.3) migraine days and acute medication days (7.9 versus 10.0) were not substantially different at baseline. The percentage of patients with at least a 50% reduction in the frequency of moderate or severe headache days was 30% for both groups (10/30 vs nine of 30, Δ 0.00, 95% CI –0.22 to 0.23). Conclusions: Greater ONB does not reduce the frequency of moderate to severe migraine days in patients with episodic or chronic migraine compared to placebo. The study was registered with ClinicalTrial.gov (NCT00915473).